3
$\begingroup$

I am trying to solve the following recurrence relations using telescoping. How would I go about doing it?

  1. $T(n) = T(n-1) + 1/n$

  2. $T(n) = T(n-1) + \log n$

thanks

$\endgroup$
4
$\begingroup$

In the first case you have $T(n) - T(n-1) = \frac{1}{n}$. If you sum with $n$ going from $2$ to $k$ you get:

$\begin{align*} \big(T(k) - T(k-1)\big) &+ \big(T(k-1) + T((k-2)\big) + \big(T(k-2) + T((k-3)\big) + \cdots + \\ &+ \big(T(4) - T(3)\big) +\big(T(3) - T(2)\big) + \big(T(2) - T(1)\big) = T(k) - T(1) = \sum_{m=2}^k \frac{1}{m}\end{align*}$

Notice how every term except $T(k)$ and $T(1)$ cancels out (I added "backwards" to make this more evident). This is the telescoping part. Then we get $T(n) = T(1) - 1 + H_n $, where $H_n$ is the $n$-th harmonic number $\displaystyle \sum_{m=1}^n \frac{1}{m}$ (I substracted $1$ because the first term $\displaystyle \frac{1}{1}$ doesn't appear in $\displaystyle \sum_{m=2}^n \frac{1}{m}$).

Likewise, in the second case you get: $\displaystyle T(n) = T(1) + \sum_{m=2}^n \log m = T(1) + \sum_{m=1}^n \log m$ (this last equality is given by $\log 1 = 0$; it doesn't make any difference but to me it looks nicer). Or you can use Cameron's hint: $T(n) = T(1) + \log n!$, by applying the product rule for logarithms.

The exact solution depends on the value of $T(1)$ in both cases.

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

Hint: a recurrence of the form $T(n) = T(n-1) + f(n)$ will have solutions $T(n) = C + \sum_{k=1}^n f(k)$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.